2020
DOI: 10.1080/23311975.2020.1747827
|View full text |Cite
|
Sign up to set email alerts
|

The role of ethical behavior and entrepreneurial leadership to improve organizational performance

Abstract: This study aims to examine the role of ethical behavior and entrepreneurial leadership in improving organizational performance. This research was conducted at the management of the Lembaga Perkreditan Desa (LPD) in Bali. Based on 2016 data, the number of LPDs in Bali was 1433 units, but 177 units were not operating, so 1256 units spread out in 9 districts/cities. Sampling is based on Slovin formula with 9% precision, so the number of LPDs sampled is 34 units. The determination of LPD samples in each district/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Integrating ethical behavior with entrepreneurial leadership is significantly able to improve organizational performance. So, ethical entrepreneurial leadership is very important in the management of the organization (Widyani et al, 2020). Based on these arguments, the research hypothesis can be built: Hypothesis 2: Ethical Entrepreneurial Leadership has a significant positive effect on organizational sustainability Some studies have found that ethical leaders can foster the trust of organizational members in their leaders (Akker et al, 2009;Engelbrecht, 2014).…”
Section: Entrepreneurial Leadershipmentioning
confidence: 99%
“…Integrating ethical behavior with entrepreneurial leadership is significantly able to improve organizational performance. So, ethical entrepreneurial leadership is very important in the management of the organization (Widyani et al, 2020). Based on these arguments, the research hypothesis can be built: Hypothesis 2: Ethical Entrepreneurial Leadership has a significant positive effect on organizational sustainability Some studies have found that ethical leaders can foster the trust of organizational members in their leaders (Akker et al, 2009;Engelbrecht, 2014).…”
Section: Entrepreneurial Leadershipmentioning
confidence: 99%
“…Previous research has found that influential entrepreneurial leaders are more likely to succeed in improving performance (Wahab & Tyasari, 2019;Widyani et al, 2020) of SMEs (Koryak et al, 2015), developing an inspiring entrepreneurial vision for the business (M. Chen, 2007), and putting forward new ideas to address challenges through creative methods (Rae, 2017). Thus, organisational performance can be enhanced (Fontana & Musa, 2017;V.…”
Section: Entrepreneurial Leadership and Organisational Performancementioning
confidence: 99%
“…The religiosity factor is a factor that influences and moderates performance (Adi & Adawiyah, 2018). Other research shows ethical rules and habits can improve company performance (Widyani et al, 2020). The existence of the economic crisis a few years ago has made Western countries take an interest in Islamic economics because Sharia firms proved to be better than non-sharia firms during the crisis (Ashraf & Khawaja, 2016;Jawadi et al, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%